2012
DOI: 10.4103/0970-0218.96095
|View full text |Cite
|
Sign up to set email alerts
|

Mass drug administration coverage evaluation survey for lymphatic Filariasis in Bagalkot and Gulbarga districts

Abstract: Background:Lymphatic filariasis (LF) is endemic in 83 countries and territories, with more than a billion people at risk of infection. In view with the global elimination, mass drug administration (MDA) with single dose of diethylcarbamazine and albendazole tablets was carried out for the eligible population in Bagalkot and Gulbarga districts.Objective:Assess coverage of MDA against LF in Bagalkot and Gulbarga districts.Materials and Methods:In this cross-sectional coverage evaluation survey, one urban and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 10 publications
3
33
3
Order By: Relevance
“…10 Compliance for both the drugs was found to be 84.6% in this study, the result being better than that observed by Patel et al in two districts of Karnataka in 2010. 1 In this study, 30.3% population swallowed drug in the presence of drug distributor (supervised coverage), which is lower as compared to study done by Ukarande et al where the same was 84.15%. 11 This difference might be due to different study settings.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…10 Compliance for both the drugs was found to be 84.6% in this study, the result being better than that observed by Patel et al in two districts of Karnataka in 2010. 1 In this study, 30.3% population swallowed drug in the presence of drug distributor (supervised coverage), which is lower as compared to study done by Ukarande et al where the same was 84.15%. 11 This difference might be due to different study settings.…”
Section: Discussioncontrasting
confidence: 46%
“…1 In India, in 2017, indigenous cases of filariasis have been reported from about 256 districts in 21 states/ Union Territories, with about 600 million people at risk of infection. 2 The Government of India is signatory to the World Health Assembly Resolution in 1997 for Global Elimination of LF.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Different studies gave different explanations for reason for non-compliance [9][10][11][12][13][14][15][16][17] In this study, only 6 persons (1.38%) had mild adverse reactions like nausea, vomiting, mild fever etc after consuming DEC. Consistent results were reported by Jothula KY etal, Prasad V G et al found 1.14%, 1.81% of adverse effects after consuming DEC. (12), (19) This study showed 86.67% households were aware regarding MDA activity from various sources like ASHA, anganwadi workers, health workers, mike announcement etc.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies across India revealed varied compliance of MDA ranging from 38.8% to 81.15%. [10][11][12][13][14][15] MDA should be implemented in more than 85% of the population in endemic areas and must be sustained for at least five years so that it will interrupt the transmission of filariasis. (3) However in this survey, the effective coverage rate was 77.78% which was lower than the standard target level.…”
Section: Discussionmentioning
confidence: 99%
“…This is much lesser than the study done by Patel (78.6%) in the Bagalkot district (2010) and higher in the Gulbarga District (38.8%) in the year 2010. 6 On the other hand, the compliance was as high as 85.6% in an independent external evaluation of MDA in Udupi district. 8 Similar observations were made by Pradeep Kumar in Gujarat state and by Mahalakshmy T at Puducherry, where compliance was 89% and 88.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%